Pengembangan Sistem Informasi Akademik berbasis Web di SMP Negeri 3 Sidikalang - Putra Sahat Mahenra Sihombing; Fajar Pradana; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
In today's era of rapidly developing information technology, the need for information is increasingly needed to support processes in achieving a certain goal. Many parties have begun to compete in developing their information technology, one of which is by developing information systems. Information system development is carried out to replace old systems that are obsolete or improve existing systems. SMP Negeri 3 Sidikalang is one of the schools that has not utilized information technology optimally. Many processes are still done manually, such as processing teacher data, student data and assessment reports obtained by each student so that it requires a lot of resources, both in terms of time, cost, energy and place. Therefore, this research aims to develop a web-based academic information system at SMP Negeri 3 Sidikalang to facilitate the school in managing data and accelerate the dissemination of information. The method used in building the system is the waterfall method, which consists of the stages of gathering needs, design, development, trial use, and maintenance. While in testing the system used SUS (System Usability Scale) method to test the level of user satisfaction. System implementation is carried out using the PHP program language with the CodeIgniter framework, database design using MySQL. Testing of academic information systems that have been built is declared feasible to use. Based on the results of the study, it can be concluded that the academic information system is feasible to use in the school environment of SMP Negeri 3 Sidikalang.